Prevalence of sleep disorders by sex and ethnicity among older adolescents and emerging adults: Relations to daytime functioning, working memory and mental health. Issue 5 (13th May 2014) - Petrov, Megan E.; Lichstein, Kenneth L.; Baldwin, Carol M.
ABSTRACT: The study determined the prevalence of sleep disorders by ethnicity and sex, and related daytime functioning, working memory, and mental health among older adolescent to emerging adult college students. Participants were U.S.A. undergraduates ( N = 1684), aged 17–25, recruited from 2010 to 2011. Participants completed online questionnaires for all variables. Overall, 36.0% of the sample screened positive for sleep disorders with insomnia, restless legs syndrome, and periodic limb movement disorder being the most prevalent. Women reported more insomnia and daytime impairment. African–Americans reported more early morning awakenings and less daytime impairment. Students with insomnia symptoms or restless legs syndrome tended to have lower working memory capacities. Students with nightmares or parasomnias had greater odds for mental disorders. In an older adolescent to emerging adult college student sample, sleep disorders may be a common source of sleep disturbance and impairment. Certain sleep disorders may be associated with lower working memory capacity and poor mental health. Highlights: Measured the prevalence of sleep disorders using standardized screening instruments. Sleep disorders and related impairment were highly prevalent among college students. Prevalence of sleep disorders varied by ethnicity and sex. Insomnia and restless legs syndrome were related to poorer working memory capacity. Nightmares and parasomnias were related to poorer mental health.